2014
DOI: 10.1093/heapol/czu013
|View full text |Cite
|
Sign up to set email alerts
|

Price subsidies increase the use of private sector ACTs: evidence from a systematic review

Abstract: Background Although artemisinin combination therapies (ACTs) are the recommended first-line treatment for uncomplicated malaria in most endemic countries, they have been prohibitively expensive in the retail sector where many suspected malaria cases purchase treatment. ACT subsidies seek to stimulate consumer demand for the drugs over cheaper but often ineffective alternatives by reducing their prices. Recent evidence from eight regions implementing such subsidies suggests that they are generally successful in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 17 publications
2
42
0
1
Order By: Relevance
“…Several trials across Africa have found that subsidies on RDTs and ACTs substantially increase their purchase and appropriate use for antimalaria treatment in retail shops. [35][36][37][38][39][40] If age-related differences are more attributable to perceptions of malaria risks, informational campaigns would be needed to encourage the use of recommended care. This study did not disentangle the reasons for different treatment-seeking choices.…”
Section: Discussionmentioning
confidence: 99%
“…Several trials across Africa have found that subsidies on RDTs and ACTs substantially increase their purchase and appropriate use for antimalaria treatment in retail shops. [35][36][37][38][39][40] If age-related differences are more attributable to perceptions of malaria risks, informational campaigns would be needed to encourage the use of recommended care. This study did not disentangle the reasons for different treatment-seeking choices.…”
Section: Discussionmentioning
confidence: 99%
“…A majority of these premises stock ACTs, following the implementation of the Affordable Medicines Facility-malaria (AMFm) program [ 38 ]. Considering that the major incentive of these premises is to maximize sales, we assume that 60–80 % of febrile children receive anti-malarial drugs [ 39 ], of which about 40–60 % are a recommended first-line drug [ 40 ]. To capture the complexity of care seeking, we assumed that half of the patients who fail to respond to treatments will choose to shift to the public health facilities and the rest will remain in the private sector.…”
Section: Methodsmentioning
confidence: 99%
“…Again this will require addressing different issues in different countries, but the index helps us see where we are succeeding in addressing the global burden of malaria, and where we are not, and creates an incentive to address relevant issues wherever they occur. [10][11][12][17][18][19]38,43,[45][46][47] CLOSING THE KNOWLEDGE GAP There are several ways the Global Health Impact malaria model might be refined, especially as better data become available, but one of the benefits of the model is to make clear the gaps in global malaria surveillance efforts. [48][49][50] It is important to move from data on efficacy from clinical trials to actual estimates of global effectiveness.…”
Section: Mechanisms For Promoting Positive Changementioning
confidence: 99%
“…[48][49][50] It is important to move from data on efficacy from clinical trials to actual estimates of global effectiveness. 46 Moreover, there is reason to move beyond a model that only credits originator companies who hold, or have acquired, the patent for these drugs. There are inevitably partner firms and others that deserve credit for the drugs' impact.…”
Section: Mechanisms For Promoting Positive Changementioning
confidence: 99%